AlHamaydeh, Mohammad - (:unkn) unknown (My University, 2026)
Mohammad AlHamaydeh earned his Ph.D. in structural/earthquake engineering from the University of Southern California, USA. He has taught several structural engineering courses, such as structural steel design, fundamentals of structural dynamics, computer methods in structural analysis and design, as well as analysis and design of tall buildings. His area of research and expertise include nonlinear structural dynamic response analysis and modeling, passive control and supplemental damping devices, computer-aided design and simulation, nonlinear finite element methods as well as soil-structure-interaction. Prior to his academic career, he was an active member of the Structural Engineers Association of California (SEAOC) as a consultant engineer in Los Angeles, California.